Adherence to lipid-lowering medication in people living with HIV: An outpatient clinic drug direct distribution experience - Gianluca Cuomo; Alessandro Raimondi; Marianna Rivasi; Giovanni Guaraldi; Vanni Borghi; Cristina Mussini (Wolters Kluwer Medknow Publications, 2021)
Objective: Adherence to lipid-lowering drugs could be challenging in our patients as it is in the general population, which is described as low as 25%. Our aim was to evaluate adherence to statins and to investigate clinical event impact on it. Methods: This retrospective study on HIV+ patients attending to Clinic of Modena (Italy) was conducted in order to evaluate characteristics, clinical events, and adherence on lipid-lowering drugs. All drugs for comorbidities are distributed by the hospital pharmacy and recorded in an electronical database. Adherence was also evaluated in patients who were supplied with antilipemics in external pharmacies through phone calls. Patients were considered adherent if the percentage of correct time of drug refill was >80%. Findings: Totally 1123 patients were evaluated. Lipid-lowering drugs (statins, fenofibrate, and omega-3 oil) were prescribed in 242 patients (21.5%). Prescription occurred mainly in those who were older, males, and Italians. Two hundred of them (82.6%) used statins alone, 23 (9.5%) only fenofibrate or omega-3 oil, and 19 (7.8%) a combination of both drugs. The median adherence was 90% while patients with adherence >80% resulted 153 (63.2%). Forty-six (19%) had a clinical history of cardiovascular events; 59% of them, placed in secondary prophylaxis, and 76%, already in treatment, continued to adhere. No differences in terms of adherence according to the type of drug distribution (hospital pharmacy or outside pharmacies) were found. Conclusion: Linking the supply of these drugs to that of antiretrovirals led to a good level of adherence higher than that described in the general population. The majority of the patients who experienced a cardiovascular event remain adherent to the prescribed therapy.